2019
DOI: 10.2215/cjn.00990119
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence, Causes, and Risk Factors of Acute Kidney Injury in Patients Receiving Immune Checkpoint Inhibitors

Abstract: Background and objectivesImmune checkpoint inhibitor use in oncology is increasing rapidly. We sought to determine the frequency, severity, cause, and predictors of AKI in a real-world population receiving checkpoint inhibitors.Design, setting, participants, & measurementsWe included all patients who received checkpoint inhibitor therapy from May 2011 to December 2016 at Massachusetts General Hospital. Baseline serum creatinine, averaged 6 months before checkpoint inhibitor start date, was compared with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
331
7
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(376 citation statements)
references
References 34 publications
30
331
7
8
Order By: Relevance
“…In a recently published study by Seethapathy et al . 1016 patients received ICI therapy at Massachusetts General Hospital, although the incidence of ICI‐related AKI was 2.95% which is similar to other reports, but surprisingly there was 17% patients who experienced AKI (defined as ≥1.5‐fold increase in creatinine from baseline), and 8.07% experienced sustained AKI (defined as an AKI event which lasted ≥3 days) …”
Section: Epidemiologysupporting
confidence: 82%
“…In a recently published study by Seethapathy et al . 1016 patients received ICI therapy at Massachusetts General Hospital, although the incidence of ICI‐related AKI was 2.95% which is similar to other reports, but surprisingly there was 17% patients who experienced AKI (defined as ≥1.5‐fold increase in creatinine from baseline), and 8.07% experienced sustained AKI (defined as an AKI event which lasted ≥3 days) …”
Section: Epidemiologysupporting
confidence: 82%
“…There was no documented period of hypotension or other prominent cause for this finding. He used a proton pump inhibitor given the gastric location of a large metastasis which could be a risk factor for AKI during CPIT (6). Despite these findings, high-dose steroids (1 mg/kg) were prescribed.…”
Section: Discussion Of Casesmentioning
confidence: 99%
“…A recent retrospective observational study showed that, in the first year after initiation of CPIs, 8% encountered a sustained AKI episode. After careful record evaluation, 3% (one in three to four sustained AKI episodes) was judged as an IRAE; however, no structural pathology data was available to validate this (6). Therefore, patients with cancer and kidney injury should undergo a careful evaluation for potential causes to make the correct diagnosis to guide appropriate management.…”
Section: Atin Is the Most Common Irae But Also Other Kidney Adverse Ementioning
confidence: 99%
“…Immune checkpoint inhibitors (ICPis) have revolutionized the treatment of cancers by engaging the patient's own immune system against the tumor (1)(2)(3). Checkpoint pathways are innate mechanisms to put the brakes on immune activation.…”
mentioning
confidence: 99%
“…Checkpoint pathways are innate mechanisms to put the brakes on immune activation. Approved agents target checkpoint pathways mediated by cytotoxic T lymphocyteassociated antigen 4 (CTLA4), programmed cell death protein 1 (PD-1), and programmed death ligand 1 (PDL-1) (1,(4)(5)(6)(7). Releasing the breaks on the immune system enhances destruction of tumor cells, but can lead to immune-related adverse effects (8,9), including renal toxicity (1,2,(10)(11)(12)(13).…”
mentioning
confidence: 99%